Communication Patterns in English Classes in Public Secondary Schools in Benguet, Philippines - Jevera Cawilan Domogen (OKARA: Jurnal Bahasa dan Sastra, 2021)
Communication patterns assume a vital role in the English classroom. It shapes the type of discourse conveyed by the teachers and the learners. This study looked into communication patterns in English classrooms and levels of questions employed in the classroom. Communication barriers and measures to address these communication barriers were identified. The descriptive method of research was utilized in the study. The study found that the students' opportunity to express themselves is limited because the communication patterns adopted in the English classroom involve initiation-response-evaluation/feedback. Students' reasoning, creative, and critical thinking skills are not honed because of the prevalence of questions in discourse. Communication anxiety and other communication barriers directly affect the communication process. Student's success in the development of their communication skills needs to be addressed. It is recommended that teachers employ communication patterns to give learners more opportunities to express ideas. The higher levels of questions should be used in the English classroom to develop their communication skills. Teachers should also employ different learning strategies to address the communication barriers and develop learners' communication skills.